Validation of targeted next-generation sequencing panels in a cohort of Polish patients with epilepsy: assessing variable performance across clinical endophenotypes and uncovering novel genetic variants - Badura-Stronka, Magdalena; Wołyńska, Katarzyna; Winczewska-Wiktor, Anna; Marcinkowska, Justyna; Karolewska, Dagmara; Tomkowiak-Kędzia, Danuta; Piechota, Michał; Przyborska, Marta; Kochalska, Natalia; Steinborn, Barbara (Frontiers in Neurology, 2024)
Targeted Next-Generation Sequencing Panels (TNGSP) have become a standard in global clinical practice. Instead of questioning the necessity of next-generation sequencing in epilepsy patients, contemporary large-scale research focuses on factors such as the size of TNGSP, the comparative advantages of exome or genome-wide sequencing over TNGSP, and the impact of clinical, electrophysiological, and demographic variables on genetic test performance. This study aims to elucidate the demographic and clinical factors influencing the performance of TNGSP in 138 Polish patients with epilepsy, recognizing the pivotal role of genetic testing in guiding patient management and therapy.A retrospective analysis was conducted on patients from a genetic clinic in Poznań, Poland, who underwent commercial gene panel studies at Invitae Corporation (USA) between 2020 and 2022. Patient groups were defined based on the age of onset of the first epileptic seizures, seizure type, gender, fever dependence of seizures, presence of intellectual disability or developmental delay, abnormalities in MRI, and the presence of dysmorphic features or congenital malformations. Seizure classification followed the 2017 ILAE criteria.Among the 138 patients, 30 (21.7%) exhibited a pathogenic or likely pathogenic variant, with a distribution of 20.7% in males and 22.5% in females. Diagnostic performance correlated with the patient's age at the onset of the first seizure and the type of seizure. Predominant variants were identified in the SCN1A,